2007
DOI: 10.1111/j.1439-0507.2007.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for candidaemia in critically ill patients: a prospective surveillance study*

Abstract: Candidaemia is frequently a life-threatening complication in patients admitted to the intensive care unit (ICU). To assess the risk factors for candidaemia in critically ill patients with prolonged ICU stay, a total of 1765 adult patients admitted for at least 7 days to 73 medical-surgical ICUs of 70 tertiary care hospitals in Spain participated in a prospective cohort study. Candidaemia was defined as recovery of Candida spp. from blood culture. Sixty-eight episodes of candidaemia occurred in 63 patients, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 46 publications
4
66
2
6
Order By: Relevance
“…2 Candidaemia is frequently a life threatening complication in patients admitted in ICUs. 1 The presence of Candida species in the urine is also common among hospitalized patients. The principal risk factors include antibiotic therapy, urinary catheterization, surgical procedures, female sex and extended hospitalization.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…2 Candidaemia is frequently a life threatening complication in patients admitted in ICUs. 1 The presence of Candida species in the urine is also common among hospitalized patients. The principal risk factors include antibiotic therapy, urinary catheterization, surgical procedures, female sex and extended hospitalization.…”
Section: Original Articlementioning
confidence: 99%
“…These pathogens are associated with increasing morbidity and mortality. 1,2 Over past two decades, there has been a change in the distribution of Candida spp. causing nosocomial infections and emerging species are C. tropicalis, C. glabrata, C. parapsilosis, C. krusei, and C. lusitaniae.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Those rules have been applied in various settings and have included assessment at different times postadmission to the ICU and different types of ICU (surgical ICUs only or mixed medical/surgical ICUs-defined as units that house both medical and surgical populations). These differences may explain why predictive models and algorithms have performed poorly outside their derivative populations (17).Since IC is preceded by colonization of mucosal surfaces with the infecting strain (14,(18)(19)(20) and since colonization is an independent risk factor for IC (14,19,21,22), it is logical that it should be incorporated into predictive models (15,16). Using data from mixed medical/surgical ICUs in Australia, we demonstrated that the post hoc addition of colonization parameters to two published clinical risk factor-only predictive models improved their performance characteristics (17).…”
mentioning
confidence: 99%
“…C andida albicans is a commensal yeast fungus that colonizes the oropharynx, intestine, and vagina in healthy individuals (1,2). In HIV-infected individuals and other immunocompromised hosts, C. albicans can be a major pathogen, causing oropharyngeal, esophageal, or vulvovaginal candidiasis (3), and it is the fourth most common cause of nosocomial bloodstream infections in the United States with a 38% mortality rate (4). Identification of the mechanisms by which the immune system protects against C. albicans infection is critical for the development of treatments and vaccines against this pathogen.…”
mentioning
confidence: 99%